We Did Not Realize about the Gender Issues. So, We Thought It Was a Good Idea: GENDER ROLES IN BURMESE OPPOSITIONAL STRUGGLES. Issue 1 (2nd January 2016) - Hedström, Jenny
Abstract: This article explores the link between nationalism, as expressed by the Burman state and ethnic and student opposition movements, and the emergence of a multiethnic women's movement engaged in resistance activities. In focusing on women's involvement in oppositional nation-making projects, this article aims to broaden our understanding of gender and conflict by highlighting women's agency in war. Drawing on interviews carried out with founding members of the women's movement, non-state armed groups and others active in civil society, the article investigates how a gendered political consciousness arose out of dissatisfaction with women's secondary position in armed opposition groups, leading to women forming a movement, not in opposition to conflict per se but in opposition to the rejection of their militarism, in the process redefining notions of political involvement and agency. By invoking solidarity based on a gendered positioning, rather than on an ethnic identity, the women's movement resisted the dominant nation-making projects, and created a nationalism inclusive of multiethnic differences. Burmese women's multiple wartime roles thus serve to upset supposed dichotomies between militancy and peace and victim and combatant, in the process redefining the relationship between gender, nationalism and militancy.